Perceived Stress and Its Associated Factors during COVID-19 among Healthcare Providers in Ethiopia: A Cross-Sectional Study - Yigrem Ali Chekole; Solomon Yimer Minaye; Semagn Mekonnen Abate; Birhanie Mekuriaw (Hindawi Limited, 2020)
Background. Coronavirus causes serious health problems worldwide including increased mental health burden to the society at large scale and particularly the healthcare providers. Understanding the immediate mental health and psychological response of the healthcare providers after a public health emergency is important for implementing better prevention and response mechanisms to a disaster. Objective. This study aimed to assess the prevalence of perceived stress and risk factors of coronavirus disease 2019 among healthcare providers in Dilla, Southern Ethiopia. Methods. An institution-based cross-sectional study was conducted among 244 samples selected with the systematic random sampling technique from March to April 2020. Data collection was carried out with a validated perceived stress scale adapted from the World Health Organization. Data were coded and entered into Epi Info Version 7 and were exported and analyzed with SPSS version 20. Crude and adjusted OR were analyzed using logistic regression, and the level of significance of association was determined at P value <0.05. Result. The prevalence of perceived stress among participants was 126 (51.6%). Being at the age range of 25-31 years (AOR = 2.5, 95% CI, 1.12, 5.81), master's and above in their qualification (AOR = 6.0, 95% CI 1.59, 22.31), nurse professionals (AOR = 8.2, 95% CI 2.69, 24.74), and pharmacist professionals (AOR = 4.8, 95% CI, 1.25, 18.64) were variables found to have a strong statistically significant association with the perceived stress of coronavirus disease. Conclusion. More than half of the study participants were found to have perceived stress for coronavirus disease. Early screening and intervention of stress among frontline healthcare providers based on the findings are suggested.